A política que passa na tv : como o Jornal Nacional reconfigurou o sentido da política nas eleições presidenciais de 2002 - Bonisem, Fabiano Mazzini (2008)
To explore the ways in which Jornal Nacional, the most prominent News TV show of Globo Television, held an unprecedented and extensive coverage of the competitive 2002 election and how they emphasize the importance of politics practices for the democracy improvement. As part of the cycle studied, there is a recognition that at stake was the attempt to restore the image of the main television station in the country, with emphasis on the construction of its new relationship with power. Part of Globo TV strategy was the adoption of an interaction model establishing new production mechanisms in the politics world through different channels of communication. Nonetheless, the absorption of politics through the media to control the public opinion is a relevant aspect of their strategy. This statement comes from analysis and the observation of discursive fragments presented in a series of reports that the Jornal Nacional aired between the months of August and October. It also reflects on the TV’s deliberation of its contents coverage during the period of election. Jornal Nacional, around the controversial election time, had the choice to whether report or leave out major issues about our country. This indicates the similarities and differences of approaches to the major issues and controversies that prevailed in special reports in relation to other Jornal Nacional coverage themes that include the pre-election campaign reports. For instance, the worsening of the economic crisis that hit Brazil in 2002 was the main instrument for limiting the discursive field in the TV news. They miss out on their approach to discuss why there were so many political candidates who weren’t able to fulfill their obligations with our nation, condition that they rather see it as a way to keep the peace in the Financial Market.